Vulnerabilities in Localization With Regard to GNSS and Harmful Radio Interference: International and EU Law Aspects - Shakila Bu-Pasha (IEEE Access, 2018)
Harmful radio interference contravenes many national, regional, and international laws. Global navigation satellite system (GNSS) services have global coverage, therefore development of international law is necessary. European Union (EU) also requires harmonized law for its member states. This paper focuses on the current state of international and EU laws to tackle GNSS, radio spectrum and radio equipment usage, and probable interference with regard to location services and privacy. From a legal point of view, this paper seeks to include mitigation of unlawful interference in radio communication in order to ensure a secured location estimation and positioning system.